2014
DOI: 10.1007/s00216-014-8379-2
|View full text |Cite
|
Sign up to set email alerts
|

Ionic strength effect on molecular structure of hyaluronic acid investigated by flow field-flow fractionation and multiangle light scattering

Abstract: This study describes the effect of ionic strength on the molecular structure of hyaluronic acid (HA) in an aqueous solution using flow field-flow fractionation and multiangle light scattering (FlFFF-MALS). Sodium salts of HA (NaHA) raw materials (∼2 × 10(6) Da) dispersed in different concentrations of NaCl prepared by repeated dilution/ultrafiltration procedures were examined in order to study conformational changes in terms of the relationship between the radius of gyration and molecular weight (MW) and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The solutions were highly shear‐thinning and showed significant viscoelastic behavior. Kim et al used field flow fractionation and multi‐angle light scattering to investigate the structure of hyaluronic acid, with the results showing both aggregation and charge‐induced molecular expansion depending upon the solution ionic strength and the molecular weight of the polysaccharide. Choppe et al showed that the relaxation time for xanthan gum increased by more than two orders of magnitude when 100 mM NaCl was added at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The solutions were highly shear‐thinning and showed significant viscoelastic behavior. Kim et al used field flow fractionation and multi‐angle light scattering to investigate the structure of hyaluronic acid, with the results showing both aggregation and charge‐induced molecular expansion depending upon the solution ionic strength and the molecular weight of the polysaccharide. Choppe et al showed that the relaxation time for xanthan gum increased by more than two orders of magnitude when 100 mM NaCl was added at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Problems of MW determination are not unique for chitosan. Contrary to DNA and proteins, which have stable conformation, polysaccharides are prone to change it in different conditions (salt, temperature, pressure) and can easily form complexes [46][47][48][49][50]. Our results demonstrate that MW may not be considered as the best characteristic of chitosan.…”
Section: Correlation Analysis Of Mw Resultsmentioning
confidence: 84%
“…for fractionation of molecular mixtures, which allows avoiding many problems in polymer analysis related to the stationary phase such as unspecific adsorption and extensive shear forces applied on large macromolecules. A FFF sub-technique, asymmetric flow field-flow fractionation (AF4) allows a fractionation of complex polymer systems according to molecular size by application of longitudinal and crossoriented flows in the channel (Kim et al, 2015;Malik & Pasch, 2016;Shin, Hwang, Cho, & Moon, 2007). The hyaluronan used in the study was characterized first using AF4 connected to MALS detectors (Wyatt, 1997) in order to obtain molecular masses, polydispersity and shape factors of the polysaccharide chains in solutions (Table 1).…”
Section: Field-flow Fractionation (Fff) Is Based On An Open-channel Techniquementioning
confidence: 99%
“…HU networks properties have already been analyzed by various techniques, e.g. rotary shadowing electron microscopy (Scott et al, 1991), X-ray crystallography (Hargittai & Hargittai, 2008), NMR spectroscopy (Almond, DeAngelis, & Blundell, 2006;Cowman, Hittner, & Feder-Davis, 1996;Nestor & Sandström, 2017;Scott & Heatley, 1999), light scattering (Kim, Woo, Park, Hwang, & Moon, 2015), tensiometry (Musilová, Kašpárková, Mráček, Minařík, & Minařík, 2019), chromatography (Shanmuga Doss, Bhatt, & Jayaraman, 2017), molecular dynamics (Cowman & Matsuoka, 2005;Hargittai & Hargittai, 2008;Kutálková, Hrnčiřík, Witasek, & Ingr, 2020) and atomic force microscopy (AFM) (Cowman, Li, & Balazs, 1998, 2005Giannotti, Rinaudo, & Vancso, 2007;Gunning, Morris, Al-Assaf, & Phillips, 1996;Jacoboni, Valdrè, Mori, Quaglino, & Pasquali-Ronchetti, 1999;Spagnoli et al, 2005;Zellermann et al, 2013). It has been proven, that despite the effect of the surface and adsorbed water described by , AFM can be used to study the aggregation and networking ability of HU with respect to the process conditions of solution preparation.…”
Section: Introductionmentioning
confidence: 99%